Development of photobioreactors and approach for large-scale production of marine algae Chrysotila and Nannochloropsis in inland environment - Chen, Xuantong (My University, 2024)
Due to energy, environment, and food problems, research on microalgae is increasingly gaining attention. Microalgae can utilize photosynthesis to synthesize and accumulate various valuable bioproducts such as lipids, proteins, polysaccharides, pigments, and can also absorb and fix carbon dioxide. Therefore, efficiently, and cost-effectively cultivating specific algae species has become a crucial goal. However, various challenges hinder the development of algae during cultivation. This study focuses on the indoor and outdoor cultivation of two marine microalgae, Chrysotila (Pleurochrysis) dentata and Nannochloropsis oceanica. For the cultivation of Chrysotila (Pleurochrysis) dentata, optimal indoor cultivation conditions were determined with a light cycle of 18 hours light / 6 hours dark, pH of 8.5, and salt concentration of 2.5 %. When Chrysotila (Pleurochrysis) dentata formed a symbiotic system with the bacterium Nitratireductor aquibiodomus, a ratio of 8:2 (algae to bacteria) resulted in optimal accumulation of dry weight, chlorophyll α, and calcium carbonate, while ratios 6:4 was more suitable for lipid accumulation. In the experiment on the impact of microplastics polyethylene terephthalate (PET) on Chrysotila (Pleurochrysis) dentata, it was observed that low concentrations of plastic (5-15 mg/L) promoted algae growth. However, high concentrations of microplastics (20-50 mg/L) slowed algal growth. [...]